EFEKTIVITAS IMPLEMENTASI PROGRAM GENTASIBU DI KELURAHAN BEGADUNG, KECAMATAN NGANJUK, KABUPATEN NGANJUK - Heylen Amildha Yanuarita; Titis Sakra (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
AbstractOne alternative to overcome malnutrition in Begadung Village, Nganjuk District, Nganjuk Health Center is running the Malnutrition Eradication Movement (GENTASIBU) program. The Gentasibu Program is a series of activities carried out in an integrated, integrated and continuous manner to maintain and improve the nutritional status of the community in the form of promotive, preventive, curative and rehabilitative efforts. The target groups in the Gentasibu program are all toddlers who have a weight index that looks very thin, for children aged 6-59 months. Gentasibu program activities at the service post such as clinical examination and treatment by doctors, antroperian measurement and counseling by nutrition officers, family empowerment by PKK Mobilizing Team, supplementary feeding (PMT) and vitamins, and mentoring of toddlers' parents by supporting cadres. In its implementation, the community or the target of the program was quite familiar with the Gentasibu program. This research uses descriptive research with a qualitative approach. Data collection techniques used are observation, interviews, documentation. The results of the study showed that socialization was carried out quite well by program implementers to the community. In the socialization, the presentation of Gentasibu program material to the target group was well received. Human resources in the implementation of the Gentasibu program are still lacking in terms of the number of Puskesmas nutrition workers. In the implementation of the Gentasibu program the authority lies with the Puskesmas nutrition officer. Keywords: Effectiveness; Implementation; Gentasibu. Abstrak Salah satu alternatif penanggulangan gizi buruk di Puskesmas Nganjuk adalah dengan menjalankan program Gerakan Pengentasan Gizi Buruk (GENTASIBU). Program Gentasibu adalah serangkaian kegiatan yang dilakukan secara terpadu, terintegrasi dan berkesinambungan untuk memelihara dan meningkatkan status gizi masyarakat dalam bentuk upaya promotif, preventif, kuratif maupun rehabilitatif. Kelompok sasaran dalam program Gentasibu adalah semua balita yang mempunyai indeks berat badan yang terlihat sangat kurus, untuk anak usia 6-59 bulan. Kegiatan program Gentasibu di pos pelayanan seperti pemeriksaan klinis dan pengobatan oleh dokter, pengukuran antroperi dan konseling oleh petugas gizi, pemberdayaan keluarga oleh Tim Penggerak PKK, pemberian makanan tambahan (PMT) dan vitamin, serta pendampingan orang tua balita oleh kader pendamping. Pada pelaksanaannya, masyarakat atau sasaran program sudah cukup paham tentang program Gentasibu. Penelitian ini menggunakan jenis penelitian deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan yaitu observasi, wawancara, dokumentasi. Hasil penelitian menunjukkan sudah cukup baik sosialisasi yang dilakukan oleh pelaksana program kepada masyarakat. Dalam sosialisasi, penyampaian materi program Gentasibu kepada kelompok sasaran dapat diterima dengan baik. Sumber daya manusia dalam pelaksanaan program Gentasibu masih kurang dalam segi jumlah petugas gizi Puskesmas. Dalam pelaksanaan program Gentasibu wewenang berada pada petugas gizi Puskesmas. Kata Kunci: Efektivitas; Implementasi; Gentasibu.